Climatic Structure Analysis of Olive Growing in Extremadura, Southwestern Spain - Fulgencio Honorio; Abelardo García-Martín; Cristina Aguirado; Luis L. Paniagua (Land)
The present study was conducted in Extremadura, a region in southwestern Spain with a significant area dedicated to olive cultivation. An analysis of the olive growing climatology of its territory was conducted using bioclimatic indices that affect the development of olive cultivation, focusing on water requirements, thermal requirements, and leaf carbohydrate synthesis. The study revealed that very dry conditions during the olive growing season are the main characteristic of the Mediterranean climate in the region. A principal component analysis was performed to analyze the main sources of variability, revealing two main components, determined by annual rainfall, annual water requirement, mean annual temperature, degree days above 14.4 °C accumulated during the olive growing season, and the number of days with optimal temperatures for leaf carbohydrate synthesis. Three homogeneous groups were determined by cluster analysis, one of which had cooler thermal conditions and no water requirements. The study found that an increase in the olive growing season or a shortening of the dormant period could result in a higher water input during the growing season and a lack of accumulation of chilling hours during the dormant period, causing crop maintenance problems in warmer locations. Climate change is expected to have significant impacts on this crop where climatic conditions are already very hot and dry. In the future, it is possible that the current olive-growing areas in Extremadura will move to other areas where the temperature is cooler.